Patriotism as the basis of political competence: the experience of the Turkish Republic - Kuruch, A. (Problems of Engineer-Pedagogical Education, 2018)
The article considers the issue of cultivating the spirit of patriotism as a component of political competence, the need to consolidate the population of Ukraine in today's difficult political and social relations. The necessity of developing the national consciousness and political culture of the population is analyzed in the paper. The article substantiates the importance of the state policy on patriotic education of the population and the need for the creation of a new unifying element. The experience of the Turkish Republic in cultivating the spirit of patriotism through the image of the national hero Mustafa Kemal Ataturk, the personality uniting the multinational population of the Turkish Republic today, is analyzed. The problem of nurturing the spirit of patriotism among Ukrainians is considered, because during the years of independence there has not been formed a nationwide idea, and most people of Ukraine have never felt to be full citizens of the state, have not been brought taking pride in their country; the population of Ukraine has been ambivalent since the Western and Northern parts of the state have shared European values whereas the Eastern and Southern parts have been oriented towards the post-Soviet states